Polysomnography findings in sleep-related eating disorder: a systematic review and case report - Blaszczyk, Bartlomiej; Wieczorek, Tomasz; Michalek-Zrabkowska, Monika; Wieckiewicz, Mieszko; Mazur, Grzegorz; Martynowicz, Helena (Frontiers in Psychiatry, 2023)
Background Sleep-related eating disorder (SRED) consists of recurrent episodes of uncontrolled, involuntary eating and drinking 1–3 h after falling asleep with partial or full unconsciousness. This condition is diagnosed based on interviews with the patients affected and the diagnostic criteria of the International Classification of Sleep Disorders. However, polysomnography (PSG) is not necessary to confirm this disease. This systematic review aims to evaluate the findings of PSG in SRED patients. Methods For this systematic review, PubMed, Embase, and Scopus databases were searched in February 2023, which resulted in 219 records. After removing duplicates, the articles that included the presentation of PSG results of SRED patients in English were selected. In addition, only original studies were considered. The risk of bias by using case reports and descriptive studies was assessed using the Joanna Briggs Institute critical appraisal tools and the Risk of Bias In Non-randomized Studies of Interventions (ROBINS-I) tool. Furthermore, a case report of a 66-year-old woman with SRED was included. Results A total of 15 papers were selected for further analysis, of which 7 were descriptive studies, 6 were case reports, and 2 were observational studies. The risk of bias in the majority of the studies was moderate or high. Unexpectedly, if the eating episode occurred during PSG, in most cases it was not observed during deep sleep (the N3 sleep stage). Moreover, studies did not report significant deviations in the sleep parameters measured using PSG. Among SRED patients, the prevalence of sleepwalking was much higher than the general population. Our case report presented a potentially life-threatening episode of holding an apple in the mouth that might result in choking, which was captured using PSG. Conclusion Polysomnography is not necessary for the diagnosis of SRED. However, it could facilitate the diagnosis and differentiation of SRED from other eating disorders. PSG also has limitations in capturing eating episodes and in addition, its cost effectiveness should be considered during the diagnostic process. More studies into the pathophysiology of SRED are needed because classifying SRED as non-rapid eye movement parasomnias can be inappropriate as it does not always occur during deep sleep.